PENGARUH PEMBELAJARAN SAS DENGAN MEDIA PAFLACA TERHADAP KEMAMPUAN MEMBACA PERMULAAN - Chasanah, Siti Nur; Rasidi, Rasidi; Triana, Putri Meinita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research aims to know the influence of learning SAS with the media Paflaca to theability to read the beginning of the 1st grade students of primary School in the Village of Tegalarum. This research is an experimental research on the design of the Pre-Experimental Design type of One-Group Pretest-posttest. This research was conducted in the Village of Tegalarum Kecamatan Borobudur, Magelang Regency. Before carrying outresearch in the village the researchers conducted observations of the pre-study onstudent Elementary school class I found the problem is reading the beginning of the stilllow. The subject of this research is the students of class I in the Village of Tegalarumwhich amounted to 16 students, which consisted of 10 female students and 6 malestudents. Data collection using the method of the test. This test is used before and after agiven treatment and the analysis used in this research is the Wilcoxon Signed Rank Testwith programSPSS version of 25.00. This research was conducted in the month of July2021. The results showed that the method of learning SAS-assisted media Paflaca affectthe ability to read the beginning. Evidence of improved student learning outcomes,namely the presence of a significant difference between the value of pretest and the valueof the posttest, namely the average value of pretest 58,1 while the average value ofposttest were 79.1 and the results of the Wilcoxon Signed Rank Test obtained value (2-tailed)-3,551 with a significance value of 0.000.